2007
DOI: 10.2139/ssrn.1019423
|View full text |Cite
|
Sign up to set email alerts
|

Smart Capital in German Start-Ups - An Empirical Analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Cumming et al (2014) attribute poorer exit performance in GVCFs to their inability to monitor, nurture, and mentor their investee businesses as effectively as IVCs. Similarly, Schäfer and Schilder () suggest that German public sector VC funds may not be as “smart” as IVCs in terms of adding value. This suggests that more should be done to enhance Lerner's principle of recruiting experienced successful high quality IVC fund managers to lead GVCF (Hood, ; Munari & Toschi, ).…”
Section: Addressing the Critique Of Government Vc—developing An Ecosymentioning
confidence: 99%
“…Cumming et al (2014) attribute poorer exit performance in GVCFs to their inability to monitor, nurture, and mentor their investee businesses as effectively as IVCs. Similarly, Schäfer and Schilder () suggest that German public sector VC funds may not be as “smart” as IVCs in terms of adding value. This suggests that more should be done to enhance Lerner's principle of recruiting experienced successful high quality IVC fund managers to lead GVCF (Hood, ; Munari & Toschi, ).…”
Section: Addressing the Critique Of Government Vc—developing An Ecosymentioning
confidence: 99%
“…Typical non-family investors such as venture capital or private equity funds are known to be interested primarily in increasing the value of their ownership stake (Wright and Robbie, 1998) and not in receiving regular distributions such as family owners not actively involved in FB management (Le Breton- Miller and Miller, 2008;Wessel et al, 2014). Moreover, venture capital or private equity investors do not only deploy capital, but also actively influence management (Cumming and Johan, 2010;Schäfer and Schilder, 2009;Tan et al, 2013). Such investors advise management not only on various topics such as accounting or marketing, but also on explorationrelated issues such as patent or technical issues -which is why money supplied by such nonfamily investors is also termed "smart money" (Schäfer and Schilder, 2009;Sørensen, 2007;Tappeiner et al, 2012).…”
Section: Family Involvement In Ownership and Organizational Ambidextementioning
confidence: 99%
“…Moreover, venture capital or private equity investors do not only deploy capital, but also actively influence management (Cumming and Johan, 2010;Schäfer and Schilder, 2009;Tan et al, 2013). Such investors advise management not only on various topics such as accounting or marketing, but also on explorationrelated issues such as patent or technical issues -which is why money supplied by such nonfamily investors is also termed "smart money" (Schäfer and Schilder, 2009;Sørensen, 2007;Tappeiner et al, 2012). In line with this notion, non-family investors regularly give advice on new corporate ventures such as internationalization and major R&D projects (George et al, 2005;De Massis et al, 2013b).…”
Section: Family Involvement In Ownership and Organizational Ambidextementioning
confidence: 99%
“…Schäfer and Schilder (2009) examined the interaction behaviours of VC funds in the case of Germany and suggested that public sector venture capital funds have a fairly similar interaction pattern with their portfolio companies to that of the bank subsidiaries. Such funds exhibit a quite high frequency of consulting in some areas (see e.g.…”
Section: Cost Theory and Geographical Proximitymentioning
confidence: 99%
“…mentoring skills, strategic insights, networks) (Pierrakis and Westlake 2009). Despite their commitment to act as commercial funds, various scholars (Mason and Harrison 2003; The role of venture capitalists in the regional innovation… Kanniainen and Keuschnigg 2004;Schäfer and Schilder 2009) suggest there is a lack of venture-capital skills in publicly backed venture capital funds, to enable effective fund management. According to Munari and Toschi (2010), even if the public intervention was targeted to companies with a real need for government aid, this financial support could be inefficiently managed by local venture capitalists due to their lack of experience and skills.…”
Section: Cost Theory and Geographical Proximitymentioning
confidence: 99%